2015
DOI: 10.3390/rs70912400
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of Two Variables Derived from Hyperspectral Data into the DSSAT-CERES Model for Grain Yield and Quality Estimation

Abstract: Abstract:The combination of remote sensing and crop growth models has become an effective tool for yield estimation and a potential method for grain quality estimation. In this study, two assimilation variables (derived from a hyperspectral sensor), called leaf area index (LAI) and canopy nitrogen accumulation (CNA), were jointly used to calibrate the sensitive parameters and initial states of the DSSAT-CERES crop model, to improve This study provides a more robust method for estimating the grain yield and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…More recently, Ban et al (2019) [30] also integrated MODIS-derived seasonal LAI as well as water stress factors into the CERES-Maize model for improved accuracy of maize yield estimations. Similar improvements with the use of data integration have been reported by Guo et al [35], Launay and Guerif [32], and Li et al [36]. Although data integration has been shown to be an effective method for enhancing site specific yield estimation, most of the previous conclusions have been drawn from state-or regional-level studies [28][29][30]34] or plot-scale experiments [36].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…More recently, Ban et al (2019) [30] also integrated MODIS-derived seasonal LAI as well as water stress factors into the CERES-Maize model for improved accuracy of maize yield estimations. Similar improvements with the use of data integration have been reported by Guo et al [35], Launay and Guerif [32], and Li et al [36]. Although data integration has been shown to be an effective method for enhancing site specific yield estimation, most of the previous conclusions have been drawn from state-or regional-level studies [28][29][30]34] or plot-scale experiments [36].…”
Section: Introductionsupporting
confidence: 60%
“…Similar improvements with the use of data integration have been reported by Guo et al [35], Launay and Guerif [32], and Li et al [36]. Although data integration has been shown to be an effective method for enhancing site specific yield estimation, most of the previous conclusions have been drawn from state-or regional-level studies [28][29][30]34] or plot-scale experiments [36]. Limited studies have been carried out to address within-field variability [35,37].…”
Section: Introductionmentioning
confidence: 56%
“…Others have used it in combination with multiple classifiers and algorithms for crop classification [25]. The most frequent application, however, is the (re-)calibration of crop models such as the WOrld FOod STudies model (WOFOST) [26], the Simple Algorithm for Yield Estimate (SAFY) [27], the Decision Support System for Agrotechnology Transfer (DSSAT) [28,29], or AquaCrop [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…At the plant level, proximal hyperspectral imaging and field spectroscopy has been used extensively to estimate plant biophysical properties and as phenotyping tool in agricultural research [73][74][75]. In an effort to assimilate these data to crop models, Li et al [76] used two assimilation variables (LAI and canopy nitrogen accumulation, CNA) derived from a field spectrometer, in DSSAT-CERES crop model to improve yield prediction of winter wheat in an area in Beijing China. The results showed that both variables were accurately estimated with spectral indices and the integration of two state variables in the model was more robust than single variable integration.…”
Section: Estimation Of Crop Parameters From Remote Sensingmentioning
confidence: 99%